From fetal threat to inadvertent actress: a case of complex maternity: De la amenaza fetal al acretismo inadvertido: un caso de maternidad compleja - Beltrán-Vidal , Álvaro Leonardo (2025)
Placenta accreta spectrum disorder (PAS) is a serious obstetric complication with an increasing incidence. The objective of this case presentation is to highlight the importance of a high index of suspicion and multidisciplinary preparation for the unexpected intraoperative diagnosis of placental accreta in a primigravida patient with no obvious risk factors. We describe the case of a 28-year-old woman at 38 weeks pregnant who, following an emergency cesarean section due to a discouraging fetal status, was found to have placental accreta that had not been diagnosed prenatally, resulting in obstetric hemorrhage requiring subtotal hysterectomy. The importance of this case lies in illustrating that PAS can occur in the absence of classic risk factors, emphasizing the need to consider this condition as a differential diagnosis for postpartum hemorrhagic complications and to have management protocols and experienced teams to optimize maternal and neonatal outcomes, even in circumstances where therapeutic options are limited by patient beliefs. Keywords: Placenta Accreta, Postpartum Hemorrhage; Cesarean Section; Pregnancy Trimester, Third (Source: MeSH, NLM).